The Effect of Target Area Training on Open Smash Accuracy in Volleyball Players - Catur Arya Ar Rassyid; Vera Septi Sistiasih; Gatot Jariono; Hanif Nugroho (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
Low open smash accuracy among volleyball athletes and the limited application of accuracy-oriented training methods remain important challenges in volleyball coaching. Previous studies have primarily focused on target-based training for serving and passing skills, whereas the application of a progressively structured target area training program incorporating variations in target position, target distance, and attack direction to improve open smash accuracy has received limited attention. Therefore, this study aimed to examine the effect of the target area training method on improving open smash accuracy among athletes of the PERBVOB Tawangmangu Volleyball Club. A quantitative approach using a quasi-experimental one-group pretest-posttest design was employed, involving 20 male athletes aged 16-23 years selected through purposive sampling. The intervention was conducted over six weeks, with two training sessions per week, resulting in a total of 12 training sessions. Data were collected using a target zone-based open smash accuracy test and analyzed using descriptive statistics, the Shapiro-Wilk normality test, a paired-samples t-test, and Cohen’s d effect size analysis with IBM SPSS Statistics version 27. The results revealed a statistically significant improvement in open smash accuracy following the intervention (p < 0.001), with a Cohen’s d value of 4.80, indicating a very large practical effect. These findings suggest that the target area training program may provide an effective approach for improving athletes’ open smash accuracy while offering a more contextual accuracy-based training model for volleyball coaching. Nevertheless, the relatively small sample size and the use of a quasi-experimental design without a control group limit the generalizability of the findings. Therefore, future studies are recommended to employ more rigorous experimental designs with control groups and larger sample sizes to further confirm the effectiveness of the target area training method.